Reformasi Struktur Parlemen, Langkah Penguatan DPD - Bambang Ariyanto (Faculty of Law Hang Tuah University, 2020)
The formation of the Regional Representative Council (DPD) as a representative body that has an equal position with the House of Representatives (DPR) is designed to accommodate regional interests in decision making at the central level. With this kind of design, the implication will be that there will be a change in the structure of parliament to move towards a bicameral parliamentary structure. However, every country that wants to adopt a representative system of both one chamber and two chambers must consider three sides, namely the function of representative institutions, membership of representative institutions, and the process of establishing laws in representative institutions. In this connection, the duties, functions, and authority of the DPD become an important issue in reviewing the parliamentary structure in force in Indonesia. Whether strengthening the parliamentary structure in the representative system in Indonesia will have implications for the functions owned by the DPD. Through normative juridical research with the legislation and conceptual approach, it is known that strengthening the parliamentary structure must be accompanied by strengthening DPD functions, specifically the legislative function, the budget function, and the supervisory function.